Simeão, o crioulo e A Escrava Isaura: o negro no romantismo brasileiro - Zahra, Lidiane Confessor de Cerqueira (2015)
This essay intends to analyze the readers "Simeão, o crioulo", by Joaquim Manuel de Macedo, published in 1869, and A Escrava Isaura, by Bernardo Guimarães, published in 1875. They report the black and the mestizo´s conditions when forming the Brazilian identity, in the nationalist romanticism. For this purpose, we referred ourselves to the base of the German romanticism with the theories of Rousseau, Kant and the Germans of Iena, pursuing to verify how much as the I romantic is toward to its inwardness, until we approach the romanticism in Brazil which uses the literature as the government's political instrument, with the responsibility to contribute for the formation of the people and to execute the establishment of the nation. It is wondered: To what extent, in those narratives, the black and the mestizo accomplish the protagonist's role in the formation of the Brazilian identity? How do they hide an image of the black / slave? In what extent does it point to the constituent values of the Brazilian romantic ideology and, especially, of Macedo and Guimarães? This work guides the hypothesis: the romantic subject's speech, by embodying the black's image, is based on the imaginary construction of the caricature, adjusting the black slave and mestizo figures. In order to oppose those ideas and to hear a voice from within the slavery, it was chosen the poem "QUEM SOU EU ?, by Luiz Gama, which exposes the existence of the slave condition. In order to handle those interrogations, it consults the critical purposes from David Brookshaw, Zilá Bernd, Antonio Cândido, Eduardo Etzel, Silvio Romero, Gilberto Freyre. As a methodological strategy, firstly it was searched the theories which sustain the commented subjects, and later to dialogue those theories with the analysis of the corpus. The suggested hypothesis is ratified, realizing it as a form of approaching the black and mestizo, both slaves, in a relationship of preservation of the nationalist ideas of the Brazilian romanticismk. The slave